Physiological and biochemical changes in coffee seed dried in silica gel and saturated saline solutions - Coelho, Stefania Vilas Boas; Figueiredo, Madeleine Alves de; Clemente, Aline da Consolação Sampaio; Coelho, Luis Filipe Serafim; Rosa, Sttela Dellyzete Veiga Franco da (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the physiological and biochemical changes in coffee seed subjected to rapid drying, in silica gel, or to slow drying in saturated saline solutions. Seeds were dried until they reached the following water contents: 40, 30, 20, 15, 10, and 5% (wet basis). After drying, part of the seeds was immediately evaluated as to their physiological performance and enzymatic profile of the oxidative process, and another part was evaluated after storage, under hermetic conditions, in freeze‑drying chamber, for four months. Drying rate and final moisture content had significant effect on seed physiological quality. After rapid drying, in silica gel, seeds tolerated lower final moisture levels. However, after slow drying, seeds with greater water levels showed higher quality. The storage period did not affect germination, but it reduced coffee seed vigor. Rapid drying shows greater damage potential to the endosperm than to the embryos. The enzymatic profile of coffee seed is affected by the final moisture level and the drying rate.